2007
DOI: 10.4140/tcp.n.2007.400
|View full text |Cite
|
Sign up to set email alerts
|

<b>Preventing Needlestick Injuries</b>

Abstract: Inadvertent puncture during use, disassembly, or disposal of needles or sharp devices (called collectively, "sharps") creates risk beyond a simple puncture. Sharps injury has always been a risk for health care workers, but emergence of certain blood-borne pathogens has intensified the need to act. Three- hepatitis B, hepatitis C, and HIV-are of utmost concern because they can cause significant morbidity or death. The incidence of sharps injury remains unacceptably high. Injury analysis at long-term care facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
0
10
0
2
Order By: Relevance
“…Factors such as type and design of needle, recapping activity and method, handling or transferring specimens or sutures, cleaning activities, manipulation of needles or sutures, passing/handling devices or failure to dispose used needle in puncture proof containers have been implicated in the causation of NSI. [1][2][3][4][5] The global estimate of such accidental exposures is nearly 3.5 million individuals. 6 In our study, a very high prevalence of NSI was found (70.3%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors such as type and design of needle, recapping activity and method, handling or transferring specimens or sutures, cleaning activities, manipulation of needles or sutures, passing/handling devices or failure to dispose used needle in puncture proof containers have been implicated in the causation of NSI. [1][2][3][4][5] The global estimate of such accidental exposures is nearly 3.5 million individuals. 6 In our study, a very high prevalence of NSI was found (70.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Avoiding recapping of needles as far as possible for disposal has been a prime emphasis in modern medical practice. 1,[8][9][10][11] Safety engineered needles and devices having features such as shields or retractable needles have proven efficacy for the prevention of these injuries. However inaccessibility and under use of such devices in the setting of Nepal may be a major contributing factor for NSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Today, over 20 blood borne pathogens have been identified as transmissible through sharps injuries, with HIV, hepatitis B virus (HBV) and hepatitis C virus (HCV) posing the highest risk of morbidity and mortality. 7 …”
Section: Risk Of Communicable Diseasesmentioning
confidence: 99%
“…However, the risk of seroconversion following needlestick injuries is much higher compared with HIV, estimated to be between 23–62%. 7,9 Furthermore, HBV can remain infective in dried blood for several days, and bodily fluids with high titers of hepatitis B antigen have the greatest risk for infectivity. 10 Finally, hepatitis C virus (HCV) transmission occurs through percutaneous or mucosal exposure, and infectivity depends on the viral load in the inoculum.…”
Section: Risk Of Communicable Diseasesmentioning
confidence: 99%